Reception of Virgil in England and Scotland c. 1400-1550: manuscripts, editions, translations - Day, M (2019)
This study examines understudied English and Scottish evidence for reading and translating Virgil in the years c. 1400-1550. Scholarship on Virgil’s reception has generally focused either on the Middle Ages or the Renaissance, but this straightforward periodisation suppresses the intellectual continuities and gradual pace of change between the two periods. The thesis assembles its broader narrative from close analyses of extant manuscripts, print editions, and translations. Using the evidence of glosses, it argues that Virgilian reading throughout the fifteenth and early sixteenth centuries was characterised more by a close attention to language than by allegory or moralisation. The linguistic focus is witnessed across a range of reading contexts both inside and outside schools, and these common glossing practices went on to shape practices of translation. The first half of the thesis is a bibliographic study of surviving manuscripts and print copies of Virgil’s Latin texts. Chapter 1 surveys the various contexts of reading Virgil manuscripts, and establishes the consistent linguistic focus of readers’ glosses. Chapter 2 shows that printing caused technological and commercial changes in book-design, but did not see major intellectual changes in glossing practice and book-use. Chapter 3 uses De Worde’s sequence of four Bucolics editions (1512-1529) to demonstrate the incremental impact of humanism on English pedagogy and print culture. Chapter 4 posits that the most striking development in fifteenth- and sixteenth-century Virgil glosses was the gradual rise in using the vernacular as opposed to Latin. The second half of the thesis demonstrates how these widespread and consistent glossing techniques influenced and informed three major Aeneid translations. William Caxton’s Eneydos (1490) is not usually considered a proper translation of Virgil, but Chapter 5 shows its frequent dependence on the Latin text and glosses. Chapter 6 demonstrates the continuities between Gavin Douglas’s Eneados (1513) and the translation practice of his fifteenth-century predecessors such as Caxton. Chapter 7 shows that the Earl of Surrey’s translations of Aeneid II and IV (c. 1543) look back to Douglas’s model, but also forward to the more rigorous formal experiments of later sixteenth-century Virgil translators. In light of these findings, the Conclusion summarises the shortcomings of applying a simplistic ‘Middle Ages’ versus ‘Renaissance’ periodisation to the reception of Virgil. It also shows that close analysis of even minute grammatical and lexical glosses is necessary to reconstruct broader trends in reading and translating classical texts.